Vigilancia de virus entéricos en aguas superficiales en Arroyo Soto, Hurlingham. - Vitali, Franco; Galeano, Fabiana Solange; Frydman, Camila Ayelén; Dus Santos, Maria Jose; Mozgovoj, Marina Valeria (Universidad Nacional de Hurlingham, 2024)
Poster